“Control químico de malezas mediante la aplicación de Mesotrione solo y en mezcla, en maíz (Zea mays L.) en la zona de Babahoyo”. - Pineda Sánchez, Jessica Angelelly (2019)
SUMMARY The present experimental work was carried out on the lands of Mr. Vicente Alarcón Estrada, located in the La Vitalia sector, belonging to the canton of Montalvo, province of Los Ríos. The geographical coordinates UTM X: 309576.93 Y: 198536.87 and is at 54 masl. The Advanta corn hybrid was used as seed material. The present experimental work had treatments (epochs of application of the products at 7, 14 and 21 days after sowing), sub-treatments (Herbicides and doses of Mesotrione at 0.25 and 0.30 L / ha, Mesotrione + Atrazine 0.25 L + 1.0 kg and 0.30 L + 1.0 kg) plus an absolute control without application of products. The experimental design of divided plots was used with three treatments, five sub-treatments and three repetitions. To perform the evaluation of the means of treatments, the Tukey test was used. The practices and agricultural tasks that were carried out in the crop were Land preparation, Sowing, Weed control, Phytosanitary control, Fertilization, Irrigation and Harvesting. Based on the results obtained, it was determined that the Mesotrione herbicide products alone and in mixture caused little toxicity in the corn culture, Advanta hybrid in the evaluations 7 and 15 days after the application; the best efficacy of the herbicides was presented with the mixture of Mesotrione + Atrazine in doses of 0.25 L + 1.0 kg in the evaluations at 15 and 30 days after applying the products; the height of the plant, height of the cob insertion, diameter and length of ear, number of grains per ear, weight of 100 grains, and grain-toe ratio stood out with the application of the product 7 days after sowing with the mixture of Mesotrione + Atrazine in doses of 0.25 L + 1.0 kg and the highest grain yield with 5180.9 kg / ha and net benefit with $ 259.2 was for the application of the Mesotrione + Atrazine mixture in doses of 0.25 L + 1.0 kg at 7 days after sowing. Keywords: weed control, mesotrione, corn.